Ryzyka i szanse w recyklingu powierzchni = Risk and chances in reuse of surface - Bauer, Dierk; Schlenker, Uwe; Szemryk, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Anthropogenic areas use is cause of many positive and negative changes in ground and in ground-waters. Often in the past terrains have been used without attention on the ecosystem functioning. Remainders from such use are often disastrous, and former users, as principals, can?t be pulled to criminal responsibility. In such situation both: private and public investors have to bear relatively big cost for restoration of these areas functionality.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); zagospodarowanie terenów; ryzyko inwestycyjne; rekultywacja terenów; area planning; investment risk; reclamation area